Pengembangan Aplikasi Perangkat Bergerak Penyebaran Informasi Kebutuhan Darah Darurat Kepada Pendonor Terdekat menggunakan Push Notification - Yanuardi Firmansyah; Agi Putra Kharisma; Wibisono Sukmo Wardhono (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
In general, when a patient needs emergency blood, a family member or friends tries to get a blood depending on the availability from the hospital where the patient is treated, to contact the Palang Merah Indonesia, post via social media, or contact the family and friends. Meanwhile PMI as a provider of blood supply is still often experience a lack of 1 million blood bags each year. In addition, asking for emergency blood through social, the results are not optimal because information on social media has been mixed with other information. The technique used in this study is waterfall model.The Application distributes emergency blood information using push notification. The push notification is used to provide a real time notification to the donor's mobile device when a blood matches the patient's blood, while the haversine formula is used to get the closest donor. The results of unit testing and validation testing method show the validity of the application is fulfilled according to the functional requirements that have been designed. based on the results of usability testing using USE, the system has fulfilled all the factors that affect usability in terms of usefulness, ease of use and satisfaction with index the average percentage is 93,12% so the system is easy to use and can used by users. And based performance testing of 8 test cases produces an average of 1,375 seconds, these results indicate the system meet the real time criteria.